Association between Metabolic Syndrome and tumor histologic grade and pathologic stage of bladder cancer - Shan Jiang; Zhi-He Xu; Qin-Feng Xu; Kun Ding; Ming-Zhen Yuan; Yong Guan; Sheng-Tian Zhao (Archive of Urological Research - Peertechz Publications, 2020)
Background: As we all know,The Metabolic syndrome (MetS) is an emerging condition worldwide, has become an important public health problem. MetS is consistently associated with an increased risk of several cancers.This study aimed to evaluate the association between the MetS and tumor grade and stage of bladder cancer. Methods: We retrospectively analyzed data of 280 patients who were diagnosed bladder cancer from the Department of Urology, Shandong Provincial Hospital between May 2013 and January 2019. Clinical staging was determined accriding to the 2002 TNM classification. Tis,Ta and T1 tumors were accepted as lower stage and T2,T3 and T4 as higher stage. The histologic grade was determined according to the 2004 World Health Organization grading system. We evaluated the predictive risk factors for the bladder cancer and MetS, including age,sex,BMI,the presence of hypertension, diabetes mellitus, High-Density Lipoprotein (HDL) and triglyceride. Analyses were completed using chi-square tests and logistic regression analysis. Results: Among the 280 patients in our study,225 were male and 55 were female. MetS was found in 84 patients. 148 patients had hpertension, 114 patients had diabetes mellitus and 129 had a body mass index ≥25 kg/m2. MetS was significantly associated with histologic stage (P=0.021) of bladder cancer.In the binary logistic regression analysis, the presence of MetS predicts the risk of higher T stage(odds ratio=0.204,P=0.001).